The effect of gluteal Kinesio-Taping on ankle function, dynamic balance, and electromyographic activity of gluteal muscles in male soccer players with chronic ankle instability: a randomized clinical trial - Zarei, H.; Lari, H.; Yoosefinejad, A. K.; Motealleh, A. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Chronic ankle instability (CAI) is associated with balance disorders and functional deficits in soccer players. Impaired gluteal muscle function contributes significantly to these issues, as these muscles play a crucial role in maintaining lower limb stability and balance. This study aimed to evaluate the effects of Kinesio-taping (KT) on the electromyographic (EMG) activity of gluteal muscles, ankle function, and dynamic balance in male soccer players with CAI.